REVIEW : PERSEBARAN PELAYANAN KESEHATAN DI DAERAH - Annisa Nurulisah; Abdul Zaky (LPPM Universitas Awal Bros, 2021)
Research conducted by Aldila Anisa Anexa Pramesti (2020) regarding the mapping of the distribution of hospitals in Kendal Regency based on a graphical information system application aims to provide information on the location of the distribution of hospitals in Kendal Regency. The results showed that Kendal Regency has 5 hospitals. Hospitals in Kendal Regency show a pattern that is spread but close together. Andi Arlyn Avila in 2017/2018 regarding the analysis of the spatial pattern of distribution and accessibility of health infrastructure service areas in Makassar City aims to identify the spatial distribution pattern of health infrastructure in Makassar City. Andy's research concludes that the spatial distribution pattern of health infrastructure in the city of Makassar is clustered. Groups of health infrastructure locations are in different locations according to the level of health services. The method used is a literature review. Literature review reviews the scientific literature on a topic and critically analyzes, evaluates, and synthesizes research findings, theory, and practice. The results of the article review show that the distribution of health services in an area is needed fairly according to the conditions and situations in that area. The community needs information related to health services in their area in order to facilitate public access to treatment.